Cerebellar Repetitive Transcranial Magnetic Stimulation and Noisy Galvanic Vestibular Stimulation Change Vestibulospinal Function - Matsugi, Akiyoshi; Douchi, Shinya; Hasada, Rikiya; Mori, Nobuhiko; Okada, Yohei; Yoshida, Naoki; Nishishita, Satoru; Hosomi, Koichi; Saitoh, Youichi (Frontiers in Neuroscience, 2020)
Background: The cerebellum strongly contributes to vestibulospinal function, and the modulation of vestibulospinal function is important for rehabilitation. As transcranial magnetic stimulation (TMS) and electrical stimulation may induce functional changes in neural systems, we investigated whether cerebellar repetitive TMS (crTMS) and noisy galvanic vestibular stimulation (nGVS) could modulate vestibulospinal response excitability. We also sought to determine whether crTMS could influence the effect of nGVS. Methods: Fifty-nine healthy adults were recruited; 28 were randomly allocated to a real-crTMS group and 31 to a sham-crTMS group. The crTMS was conducted using 900 pulses at 1 Hz, while the participants were in a static position. After the crTMS, each participant was allocated to either a real-nGVS group or sham-nGVS group, and nGVS was delivered (15 min., 1 mA; 0.1–640 Hz) while patients were in a static position. The H-reflex ratio (with/without bilateral bipolar square wave pulse GVS), which reflects vestibulospinal excitability, was measured at pre-crTMS, post-crTMS, and post-nGVS. Results: We found that crTMS alone and nGVS alone have no effect on H-reflex ratio but that the effect of nGVS was obtained after crTMS. Conclusion: crTMS and nGVS appear to act as neuromodulators of vestibulospinal function.